Using eye tracking as an aid to pre-test choice experiments: an application to an online DCE on small ruminants’ meat - Cubero Dudinskaya E.; Naspetti S.; Zanoli R. (Efficiency and resilience of forage resources and small ruminant production to cope with global challenges in Mediterranean areas, 2021)
The decrease in small ruminant’s meat consumption in Europe during the last decades has been accentuated by consumers perception of small ruminant’s meat as a traditional product, difficult to cook and with high prices. Additionally, the wide range of products and labels in the market, has forced consumer to rely on larger set of products’ characteristics. However, given the limited capacity of the brain, not all this information can be processed. Our main objective is to understand which attributes consumers are interested in when selecting lamb/sheep meat. Through a Discrete Choice Experiment (DCE) using eye-tracking, we compared the stated preferences of the respondents in the DCE, the self-reported statements on non-attendance and their visual attention to each attribute and levels. We estimated a multinomial logit model (MNL) in R, that was used to design a final DCE. The data was collected in seven European countries (Finland, France, Greece, Italy, Spain, Turkey and United Kingdom) and analysed through MNL. Results show differences between the preferred attributes in each country. Only the price attribute was significant for all countries. We also found differences between the respondents self-reported statements and their visual attention.
1. Joint meeting of the FAO-CIHEAM Networks on Sheep and Goats (Subnetworks on Nutrition and Production Systems) and on Mediterranean Pastures, 2019/10/23-25, Meknes (Morocco)